Synthesis and Spectroscopic Characterization of New Axially Coordinated Cobalt(III) Schiff Base Complexes - Esmati, N.; Yousefi, M.; Shafiee, A.; Foroumadi, A. (Asian Journal of Chemistry, 2011)
Cobalt(III) complexes with tetradentate Schiff bases, H2L, derived from salicylaldehyde and diamines such as 2,3-diaminopyridine, 2,3-diamino toluene and 3,4-diaminotoluene have been synthesized and characterized by IR and 1H NMR spectroscopy and elemental analysis. The experimental results support the binding of ligands with two N and two O donor sites to cobalt ion.